2021
DOI: 10.1108/bfj-11-2020-0992
|View full text |Cite
|
Sign up to set email alerts
|

Young consumers' perception of food safety and their trust in official food control agencies

Abstract: PurposeThe purpose of the research was to investigate how young consumers perceive food safety and if they trust that official food control agencies or other actors of food supply chains ensure a proper level of safety of food in Poland. The purpose of the paper was also to find out if young consumers are currently concerned that a proper level of food safety is not ensured.Design/methodology/approachThe analysis was based on a data set from 650 questionnaires collected in an online survey carried out in Octob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Nevertheless, improving food safety and sustainability necessitates the participation and cooperation of a wide range of stakeholders, including the food industry but also the household level. In a recent study [15], young generations showed little concern about food safety and limited trust in food control agencies. They hold food producers and food processing companies as mainly responsible for food safety, while retailers and consumers were perceived as the least responsible ones.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, improving food safety and sustainability necessitates the participation and cooperation of a wide range of stakeholders, including the food industry but also the household level. In a recent study [15], young generations showed little concern about food safety and limited trust in food control agencies. They hold food producers and food processing companies as mainly responsible for food safety, while retailers and consumers were perceived as the least responsible ones.…”
Section: Introductionmentioning
confidence: 99%
“…Food safety is very important because the food we eat has an impact on our health. Food safety is a significant characteristic of food for consumers (Badrie et al, 2006;Grunert, 2005;Rohr et al, 2005;Bukachi et al, 2021;New Food Magazine, 2021;Bolek, 2020;Franc-Da ˛browska et al, 2021;Jenkins et al, 2021). The high importance of food safety is caused by the fact that food is a product that satisfies one of the most important physiological needs of a humanthe need to eat (Maslov, 2009).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…, 2005; Bukachi et al. , 2021; New Food Magazine, 2021; Bolek, 2020; Franc-Dąbrowska et al. , 2021; Jenkins et al.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Nevertheless, improving food safety necessitates the cooperation of a wide range of stakeholders, including the household level. The results of a recent study (Franc-Dabrowska et al, 2021) highlight that public awareness is needed, and food chain stakeholders need to be trained and organized to contribute to the collective effort required to improve food safety from farm to fork. This is why in the present paper, the focus is on perceptions of infant food safety for different food products at the level of infant food users and primarily parents.…”
Section: Introductionmentioning
confidence: 99%